2018
DOI: 10.1136/bmjopen-2017-018323
|View full text |Cite
|
Sign up to set email alerts
|

Association between perceived stress, multimorbidity and primary care health services: a Danish population-based cohort study

Abstract: ObjectivesMental stress is common in the general population. Mounting evidence suggests that mental stress is associated with multimorbidity, suboptimal care and increased mortality. Delivering healthcare in a biopsychosocial context is key for general practitioners (GPs), but it remains unclear how persons with high levels of perceived stress are managed in primary care. We aimed to describe the association between perceived stress and primary care services by focusing on mental health-related activities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 69 publications
3
47
0
Order By: Relevance
“…13 Regarding the perceived stress, we found PSS scores again significantly higher compared to those in a recent study in the Danish population (median of 11). 17 Our findings reveal that sleeping less than seven hours per night has a correlation with PSQI greater than 5. Furthermore, the number of weekly work hours, taking sleep medication and perceived stress are independent risk factors for "poor" quality of sleep, in contrast to sleeping more hours per night, which is protective.…”
Section: Discussionmentioning
confidence: 49%
“…13 Regarding the perceived stress, we found PSS scores again significantly higher compared to those in a recent study in the Danish population (median of 11). 17 Our findings reveal that sleeping less than seven hours per night has a correlation with PSQI greater than 5. Furthermore, the number of weekly work hours, taking sleep medication and perceived stress are independent risk factors for "poor" quality of sleep, in contrast to sleeping more hours per night, which is protective.…”
Section: Discussionmentioning
confidence: 49%
“…One in fifty may not sound as many, but this figure corresponds to almost one patient per week per GP and around 75,000 patients in Denmark during 6 months. Patients with stress often requires several consultations, including examinations of psychological and physical symptoms, talk therapy, introduction and adjustment of pharmaceutical treatment, sick notes and declarations to employer and municipality; psychological stress is associated with high use of both elective and acute services by the GP and in the hospitals [29, 30]. This reflects a substantial burden on society at large and on general practice in specific.…”
Section: Resultsmentioning
confidence: 99%
“…Higher scores are known to be associated with depressive symptoms related to current life situations. 29 Alkhathami et al, through a study of 368 primary healthcare patients with diagnosed hypertension and diabetes, demonstrated that patients who were aware of their uncontrolled HTN or T2DM had increased levels of perceived stress and this was associated with increased prevalence of depression and anxiety. This feeling had no correlation with objective measures of control like glycated hemoglobin and measured blood pressure.…”
Section: Discussionmentioning
confidence: 99%